Midwives’ and mothers’ perspectives on skin-to-skin care of premature and low-birthweight infants in Puntland, Somalia - Osman, Fatumo; Egal, Mohamed Said; Abdi, Ahmed Ali; Mohamud, Anisa Abdikarim; Erlandsson, Kerstin (Somali Health Action Journal, 2021)
Background: More than 2.5 million children die yearly due to prematurity and low birthweight. Skin-to-skin care provides a thermal-control environment that offers protection from infection and eases breast milk feeding to the advantage of the new-born. Aim: This study aimed to explore barriers and facilitating factors for introducing skin-to-skin care of premature and low-birthweight infants based on input from mothers and midwives in Puntland, Somalia. Methods: Qualitative semi-structured interviews with four mothers and four midwives were analysed using qualitative content analysis. Results: The findings are presented in four categories: enabled by support and hands-on information to the mother and her family; aided by collaboration with the mother’s family to overcome the mother’s resistance; impeded by limited time, lack of resources and unavailable guidelines; and hindered by traditional and social beliefs. Both mothers and midwives emphasised the importance of information and education concerning skin-to-skin care of premature and low-birthweight infants. Family members and midwives facilitated skin-to-skin contact as the care model. The degree to which the midwives provided information to the mothers and their family members depended on how the two latter groups received and acted on such information and education. Lack of motivation by mothers, their families or midwives were barriers to skin-to-skin contact as a care model. Conclusion: Standardised guidelines, preferably culturally tailored for low socioeconomic groups, for midwives’ use when informing mothers and families on skin-to-skin contact as a care model for premature and low-birthweight infants would empower women, families and midwives to facilitate the practice in Puntland, Somalia.